A Review of Non-Invasive Haptic Feedback stimulation Techniques for Upper Extremity Prostheses - Nemah, Mohammed Najeh; Low, Cheng Yee; Aldulaymi, Omar Hammad; Ong, Pauline; Ismail, Al Emran; Qasim, Abdullah Ali (International Journal of Integrated Engineering, 2019)
A sense of touch is essential for amputees to reintegrate into their social and work life. The design of the next generation of the prostheses will have the ability to effectively convey the tactile information between the amputee and the artificial limbs. This work reviews non-invasive haptic feedback stimulation techniques to convey the tactile information from the prosthetic hand to the amputee’s brain. Various types of actuators that been used to stimulate the patient’s residual limb for different types of artificial prostheses in previous studies have been reviewed in terms of functionality, effectiveness, wearability and comfort. The non-invasive hybrid feedback stimulation system was found to be better in terms of the stimulus identification rate of the haptic prostheses’ users. It can be conclude that integrating hybrid haptic feedback stimulation system with the upper limb prostheses leads to improving its acceptance among users.